1981
DOI: 10.1071/bi9810047
|View full text |Cite
|
Sign up to set email alerts
|

Sulfur and Methionine Metabolism in Sheep. V. Utilization of Methionine Isomers

Abstract: Merino wethers were fed 600 g dry matter per day of a ground and pelleted 50 : 50 oaten chaff: lucerne chaff diet. The ration was fed in 12 equal protions at 2-hourly intervals. The diet of some sheep was supplemented with infusions of 2�5 g/day of either L-, DL- or D-methionine into either the rumen or duodenum. Ruminal sulfide-sulfur pools, the amount of sulfur flowing at the duodenum and excreted in faeces and urine, and the amount of sulfur incorporated into wool were measured. [35Sl-LMethionine injections… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1984
1984
2012
2012

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…High bioavailability of d-Met has been reported in mouse, rat, chick, rabbit, dog, and pig (see Lewis and Baker, 1995), with these usually assessed by comparison of N retention or weight gain obtained with the various enantiomers. Similarly, in sheep, a mixture of dl-Met or d-Met was as effective as l-Met to support wool growth (Doyle, 1981;Reis et al, 1989), although Doyle (1981) reported a trend toward lower S and N retention with d-versus l-Met supplementation. In cattle, postruminal infusion of dl-Met tended to result in a lower N retention than observed with l-Met supplementation (Titgemeyer and Merchen, 1990) but, in a second study, d-Met was 96% as efficient as l-Met in supporting N retention (Campbell et al, 1996).…”
Section: Studymentioning
confidence: 92%
See 1 more Smart Citation
“…High bioavailability of d-Met has been reported in mouse, rat, chick, rabbit, dog, and pig (see Lewis and Baker, 1995), with these usually assessed by comparison of N retention or weight gain obtained with the various enantiomers. Similarly, in sheep, a mixture of dl-Met or d-Met was as effective as l-Met to support wool growth (Doyle, 1981;Reis et al, 1989), although Doyle (1981) reported a trend toward lower S and N retention with d-versus l-Met supplementation. In cattle, postruminal infusion of dl-Met tended to result in a lower N retention than observed with l-Met supplementation (Titgemeyer and Merchen, 1990) but, in a second study, d-Met was 96% as efficient as l-Met in supporting N retention (Campbell et al, 1996).…”
Section: Studymentioning
confidence: 92%
“…For ruminants, data are scarce and somewhat equivocal. For example, in sheep, lower utilization of d-Met than l-Met has been reported for both N and S retention (Doyle, 1981) although they appear equally effective for support of wool growth (Doyle, 1981;Reis et al, 1989). In growing cattle, d-and l-Met produced similar increases in N retention (Campbell et al, 1996) although this tended to be lower with dl-Met infusion compared with an equimolar dose of l-Met (Titgemeyer and Merchen, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…D-Methionine was as effective as Lmethionine for stimulating the synthesis of the ultrahigh-sulphur proteins in wool (Broad, Gillespie & Reis, 1970). More recently, Doyle (1981) has found that L-, D-and DL-methionine were equally effective for enhancing wool growth and increasing the sulphur content of wool. There would now seem to be sufficient evidence to conclude that D-and L-methionine are equally effective for enhancing wool growth.…”
Section: Discussionmentioning
confidence: 97%